Human drama in art of the blind painters Sargy Mann and John Bramblitt and in Fr. Józef Tischner’s reflections - Wołczyńska, Anna (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2018)
Nothing intrigues more than performing tasks that disability renders impossible. Overcoming physical limitations and mental restraints raises an interesting issue of the human creative potential broadly investigated by scientists and acutely experienced by the disabled. A cruel disease that leads to complete blindness appears even more dramatic when affects visual artists. A blind artist painter sounds an oxymoron, but the stories of Sargy Mann and John Bramblitt prove that a human being can always defy comfortable schemes. A sighted observer may be puzzled by complexity of this multipolar drama marked with painful turning points, but also, perhaps surprisingly, with a feeling of gain, sense, and reward. The artists’ personal and subjective perception of the loss inspires a discussion that presents universal values in a broader perspective. Beauty and truth, uncertainty and courage are to be found in the narrations of the artists above and the essays of a distinguished Polish philosopher Fr. Józef Tischner. The article portrays the silhouettes of the blind painters focusing on their artistic strive to a meaningful and rewarding life in the light of philosophical reflections based on the axiomatic concepts of beauty and truth.